Low-intensity Treadmill Exercise-related Changes in the Rat Stellate Ganglion Neurons - de Oliveira Cavalcanti, Renato Albuquerque; da Pureza, Demilto Yamaguchi; de Melo, Mariana Pereira; de Souza, Romeu Rodrigues; Bergamaschi, Cassia T.; Amaral, Sandra Lia do [UNESP]; Tang, Helen; Loesch, Andrzej; Coppi Maciel Ribeiro, Antonio Augusto (Wiley-liss, 2009)
Stellate ganglion (SG) represents the main sympathetic input to the heart. This study aimed at investigating physical exercise-related changes in the quantitative aspects of SG neurons in treadmill-exercised Wistar rats. By applying state-of-the-art design-based stereology, the SG volume, total number of SG neurons, mean perikaryal volume of SG neurons, and the total volume of neurons in the whole SG have been examined. Arterial pressure and heart rate were also measured at the end of the exercise period. The present study showed that a low-intensity exercise training program caused a 12% decrease in the heart rate of trained rats. In contrast, there were no effects on systolic pressure, diastolic pressure, or mean arterial pressure. As to quantitative changes related to physical exercise, the main findings were a 21% increase in the fractional volume occupied by neurons in the SG, and an 83% increase in the mean perikaryal volume of SG neurons in treadmill-trained rats, which shows a remarkable neuron hypertrophy. It seems reasonable to infer that neuron hypertrophy may have been the result of a functional overload imposed on the SG neurons by initial posttraining sympathetic activation. From the novel stereological data we provide, further investigations are needed to shed light on the mechanistic aspect of neuron hypertrophy: what role does neuron hypertrophy play? Could neuron hypertrophy be assigned to the functional overload induced by physical exercise? (C) 2008 Wiley-Liss, Inc.
Keywords: stereology; extrinsic cardiac innervation; physical exercise; stellate ganglion; rats